Mass Spectrometric Characterization of Metabolites in Ear Cartilage: Congenital Microtia and Normal Auricle. Issue 1 (July 2020) - Yang, Jinxiu; He, Leren
Abstract : Objective: The aims of the study were to perform mass spectrometric characterization of metabolites in microtic and healthy ear auricular cartilage tissue, to screen the differential metabolites and pathways in these tissues, and to find a connection between the changes in the metabolic pathways and the biochemical properties of the cartilage tissue. Methods: According to the inclusion criteria, patients with simple microtia admitted to the hospital between June 2017 and January 2018 were selected upon admission. During ear reconstruction surgery, residual auricle cartilage tissues of the patients were harvested as the case group (18 cases), and normal auricle cartilage tissues (18 cases) were taken as the control group. The mass spectrometry technique gas chromatography time-of-flight mass spectrometry and the Xplore MET platform were used to identify and characterize the metabolites in the ear cartilage samples. Then, differential metabolites and key pathways were identified and analyzed. Results: In total, 277 metabolites were detected, but only 132 metabolites were annotated in the JiaLib (one of the largest metabolomics libraries in the world). Of those, 14 differential metabolites and 3 metabolic pathways were identified between microtia and healthy ear cartilage, including the pathways of arginine metabolism, taurine metabolism, and pantothenate and CoA metabolism, P < 0.05. Conclusions: Arginine, taurine, and L-cysteine may have an association with the development of microtia ear cartilage, and arginine succinate synthase and argininosuccinate lyase may be the key enzyme in microtia. This new direction on microtia can help us understand the pathogenesis of microtia and propose some new ideas for its etiology.